Scenario planning of investment at pt. Pertamina refinery directorate - RM Dony, RM Dony; Sunitiyoso, Yos (The Indonesian Journal of Business Administration, 2016)
Abstract - Currently energy consumption especially in Indonesia tends to increase from year to year, due to advances in technology and science, almost all aspects of life requires energy, such as for electricity generation, transport, commercial activities, industry and domestic purposes. The energy consumption tends to have a significant increase in the last 10 years, so the company must invest in order to increase production capacity so as to meet the consumer demand. Scenario planning analysis is used to develop strategies for a period of five years. Based on some influencing factors that identified from interview, two key uncertainties can be developed which are 'demand for fuel' and 'investment feasibility’. Both key uncertainties then plotted into four quadrants with the positive and negative extreme conditions to get the four scenarios, namely 'head down and recovered'; 'preparation for the future'; 'remain calm and move slowly' and 'growth ahead'. Of the four scenarios can be formulated three possible strategies to be applied by a company which are major investment, the selected investments and focus on operations. Major investment strategy focused on increasing production capacity in addition also to increased complexity and flexibility of existing facilities or build new refineries. The selected investment strategy is generally more focused on increasing the complexity and flexibility of the existing facilities. Focus on the operational strategy generally focused on operations rather than investment concerned with efficiency and product diversification. Implementation plan is needed to describe in more detail all strategies that already developed to be fitted to the entire scenario that may face by the company in the future. Keyword: energy, scenario planning, investment, refinery, strategy.